Skill development in mathematical work: the case of Lucas, a prospective mathematics teacher in training practice - Verdugo-Hernández, Paula (2023)
[Objetive] This study seeks to characterize the mathematical work that prospective mathematics teachers prioritize in their initial training practices, in particular in the final stage of these practices (professional practice), as shown in their teaching proposals related to the development of disciplinary (mathematical) skills established in the Chilean curriculum. [Methodology] This is a qualitative study which analyzes the implementation of an online class on position measurements (quartiles) and its corresponding planning. A content analysis of mathematical tasks studied in the class was carried out, focusing on their characteristics and the disciplinary skills specified in the planning stage. [Results] Results show that the mathematical work emphasized on these tasks addresses skills that are different from those which were planned. In addition, low levels of student participation in the on-line classes lead prospective teachers to solve the proposed tasks by themselves, hindering the development of the mathematical skills specified in the planning stage. [Conclusions] The mathematical work proposed in the selected tasks promotes use of semiotic representations and operational aspects of the quartiles, but remains unconnected to the development of disciplinary skills. Finally, the selection of tasks that engage students and allow development of planned skills by the prospective teacher are considered, taking into account the abilities that the teacher expects to develop during teaching, to motivate the observation of teachers’ training processes.